Pengukuran Road User Satisfaction Index Jalan Jawa Kabupaten Jember - Zainuddin Permana, Muhammad; Hamduwibawa, Rofi Budi; Gunasti, Amri (Indonesian Journal Publisher, 2024)
Java Road is one of the roads located in Sumbersari District, Jember Regency, which is very busy and strategic, causing several problems, such as congestion, noise, traffic accidents and other things. Research on the level of satisfaction of Javanese road users is an urgent matter that must be done. The aim of this research is to analyze the level of importance and performance of Javanese roads. In this research, the basis for making the instrument was based on interviews with stakeholders and based on the RUSI (Road User Satisfaction Index) standard which had been used in previous research. The research results show that the Road User Satisfaction Index (RUSI) value on Javanese roads is 58.50. The RUSI value is in the range between 51-65.99 percent with quite satisfactory criteria.